Creep properties of cement and alkali activated fly ash materials using nanoindentation technique - Lee, Hyuk; Vimonsatit, Vanissorn; Chindaprasirt, P.; Ngo, T.; Mendis, P. (Elsevier BV, 2018)
This paper presents creep properties of cement and alkali activated fly ash (AAFA) paste and mortar determined from statistical analysis of nanoindentation data. Cement paste having 95 MPa compressive strength at 28 days was tested for comparison and validation with a conventional test. Using nanoindentation, the specific creep of the cement paste after one year was predicted as 18.32 microstrain/MPa. For AAFA samples, an experimental program was set up using Taguchi's Design of Experiment method to consider four parameters, silica fume, sand to binder ratio, liquid to solid ratio, and superplasticiser, each with three variations.Using ANOVA, the percentage contributions of these parameters on the creep modulus of AAFA samples are: silica fume 26%, sand to binder ratio 21%, liquid to solid ratio 22%, and superplasticiser 31%. The results using de convolution technique to identify the creep modulus of different phases of AAFA matrices show that partly-activated, non-activated slag and non-activated compact glass phases are leading the creep behaviour of AAFA samples due to their high creep modulus. Compare to other parameters, the liquid to solid ratio contributes the most to the creep property of partly-activated slag, non-activated slag and non-activated compact glass phases, that is, 51%, 89%, 68%, respectively. Sand to binder ratio and superplasticiser have minor effect on the creep behaviour. The results of the creep properties of AAFA paste were then compared with those of AAFA concrete using an upscaling process. The creep rate of AAFA concrete was defined by the creep properties of the matrix and the interface between aggregates and matrix assuming perfect bonding and slip bonding conditions. The results from the upscaling process show that the creep properties of AAFA paste from nanoindentation are representative of the long-term creep properties of AAFA concrete determined from a conventional test method.